O invisível como impulso afetivo: em busca da gênese da intencionalidade - Oliveira, Josiana Hadlich de (2024)
This thesis aims to present a new notion of “invisible” as an affective impulse that has a necessary function in the genesis of intentionality. To configure a phenomenology that encompasses such ideas, the research aimed to understand, especially in the interpretation and extension of the thoughts of Merleau-Ponty and Renaud Barbaras, how affectivity can reveal a deep dialectic between self-affection and hetero-affection. This dialectical process describes the way in which the living subject affects himself (self-affection) and, simultaneously, opens himself to the other and the world (hetero-affection), founding conscious experience in a relational dynamic. Thus, in what we will call dialectical affectivity, we have the chiasm between visible and invisible in a relationship that transcends a simple objective perception. The invisible, then, is not just that cannot be seen, that is absent or that is hidden, but it is the “something” that affects consciousness, pushing it to carry out an activity in passivity from hetero-affection directed towards selfaffection and, therefore, Consequently, the self-affection already in activity turns to hetero-affection, originating to intentionality. This movement is dialectical, not static. Hence, affectivity is dialectical, it is a movement that has no synthesis, where intentionality itself is consolidated in this reciprocal movement between self-affection and hetero-affection.